Perceived stress, mental health, and job satisfaction among lawyers working in public versus private sector - Nidhi Malhotra; Shikha Tyagi; Ekram Goyal; Gurmeet Kaur; Jagtar Singh; Suprakash Chaudhury (Industrial Psychiatry Journal)
Background: Lawyers are exposed to a multitude of stressors; hence, a high proportion of them experience mental health issues and dissatisfaction with their jobs. However, no data compare these parameters in private and public sector lawyers from India. Aim: To compare mental health status, perceived stress, and job satisfaction in public versus private sector lawyers. Materials and Methods: Thity participants, each from lawyers working in the public and private sectors in Chandigarh, were recruited and administered a sociodemographic scale, General Health Questionnaire 12, Cohen’s Perceived Stress Scale, and Generic Job Satisfaction Scale. Results: 73% and 60% of participants scored more than two on GHQ in the public and private sector groups, respectively. A significantly higher (90%) proportion of lawyers working in the public sector experienced high levels of stress when compared with lawyers working in the private sector (63%). A negative correlation between stress levels and job satisfaction was observed in both groups. Conclusion: Lawyers experience high levels of stress and mental health issues, with stress being more prevalent in public sector lawyers. There is a negative correlation between stress levels and job satisfaction in private and public sector lawyers.